2017
DOI: 10.1186/s13722-017-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing patient navigation to improve intervention session attendance and viral load suppression of persons with HIV and substance use: a secondary post hoc analysis of the Project HOPE study

Abstract: BackgroundInterventions are needed to improve viral suppression rates among persons with HIV and substance use. A 3-arm randomized multi-site study (Metsch et al. in JAMA 316:156–70, 2016) was conducted to evaluate the effect on HIV outcomes of usual care referral to HIV and substance use services (N = 253) versus patient navigation delivered alone (PN: N = 266) or together with contingency management (PN + CM; N = 271) that provided financial incentives targeting potential behavioral mediators of viral load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…They indicate that, from the navigator’s point of view, the incentives were helpful for increasing positive behaviors, including attendance at navigation sessions and HIV care visits, particularly for participants who were financially disadvantaged or lacking in other motivators, but were less helpful for addressing the unhealthy behavior of drug use. The viewpoints expressed by navigators are generally consistent with objective findings from secondary data reported in the main study outcomes paper (Metsch et al, 2016) and post-hoc analyses (M. Stitzer, Matheson, et al, 2017; M.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…They indicate that, from the navigator’s point of view, the incentives were helpful for increasing positive behaviors, including attendance at navigation sessions and HIV care visits, particularly for participants who were financially disadvantaged or lacking in other motivators, but were less helpful for addressing the unhealthy behavior of drug use. The viewpoints expressed by navigators are generally consistent with objective findings from secondary data reported in the main study outcomes paper (Metsch et al, 2016) and post-hoc analyses (M. Stitzer, Matheson, et al, 2017; M.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the objective data on patient navigation session attendance (M. Stitzer, Matheson, et al, 2017) patient navigators reported that the financial incentives helped motivate people to attend navigation sessions early on.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Contingency management, the strategy of rewarding people for desired behaviors, was a key component of Project HOPE, a NIDA Clinical Trials Network study that used peer navigators to link hospitalized patients with untreated HIV and substance use disorders to HIV treatment. Providing monetary incentives to attend peer navigator sessions increased visit attendance and HIV viral suppression at 6 months [ 12 ]. Similar strategies might be tested in outpatient HIV clinics where the prevalence of substance use disorders remains high.…”
mentioning
confidence: 99%
“…Multiple studies have focused on systems-level changes to improve HIV retention in care including providing onsite comprehensive services and reducing structural barriers via patient navigation (Gardner et al, 2005; Higa, Marks, Crepaz, Liau, & Lyles, 2012; Willis et al, 2013). Financial-based contingency management approaches have also demonstrated efficacy in promoting treatment engagement and viral suppression in patients with comorbid HIV and substance use disorder (SUD; (Stitzer et al, 2017). A recent systematic review reported that only three studies have tested contingency management interventions among PLWH with a comorbid substance use disorder (Herrmann et al, 2017).…”
Section: Hiv Care Retention Strategiesmentioning
confidence: 99%